Delayed uterine rupture and septic shock after high-intensity focused ultrasound for uterine fibroids: a case report - Xia, Huan; Liu, Wenyin; Mao, Hui; Li, Chi; Zu, Yizheng; Yu, Yi; Chen, Wanying; Zhang, Yaoyang; Chen, Jiming (Frontiers in Oncology, 2025)
BackgroundHigh-intensity focused ultrasound (HIFU) ablation is widely regarded as a safe and minimally invasive technique for treating uterine fibroids. However, severe complications such as uterine rupture and septic shock remain exceedingly rare.Case presentationWe report a case of a 42-year-old woman who developed uterine rupture complicated by septic shock one month after undergoing HIFU ablation for uterine fibroids.ConclusionsAlthough HIFU ablation for uterine fibroids is widely considered a safe and minimally invasive procedure, clinicians should recognize the potential for severe complications, including uterine rupture and septic shock.